PERMAINAN MARGALA SEBAGAI UPAYA PENANAMAN DAN PEMBENTUKAN KARAKTER SISWA - Priska Nurlia Br Simanungkalit; Daulat Saragi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Margala is a traditional Batak game played by two groups and the number of players is determined by the number of field squares which are full of meaning and character values, through this game the character of students will be instilled and formed properly, because by instilling character values to students, it will produce and form graduates who have good and polite character. This study is a qualitative study with the form of a library study with the object of study being students of SD Negeri 055981 Beruam, the results of the study explain that there are very many character values contained in the traditional game of margala including discipline, social, honesty, cooperation and sportsmanship.